BEBERAPA FAKTOR PENENTU KEBERLANJUTAN USAHA AGROINDUSTRI TEH RAKYAT - Lucyana Trimo; Syarif Hidayat; Muhammad Arief Budiman (Universitas Galuh Ciamis, 2019)
At present the number of actors from the tea agro-industry actors in West Java is decreasing, for example, the agroindustry of tea smallholder in Cianjur District in 2015 in Sub-districts: Sukanagara only has six units out of 11 units, Takokak Sub-district there are only 11 units of 38 units, and The Campaka sub-district has no more agroindustry of tea smallholder that was established even though a few years ago there were three units of the agroindustry of tea smallholder. These conditions also occur in other areas, such as in Bandung's Ciwidey District, even now only the Barokah Farmers Group's agroindustry still survives (from the four agro-industries in Bandung's Ciwidey District). Some determinants of the persistence of the agroindustry of tea smallholder can come from internal and external factors concerned. The research technique used is a case study. Determination of informants was done purposively, namely Plantation Service staff, chairman and deputy chairman of the farmer group, general manager of the tea agro-industry of the people, supplier farmers, and village apparatus. Secondary data is collected from existing documents in relevant agencies and journals. Data and information obtained were analyzed descriptively. The results showed that, the sustainability of the existence of the agroindustry of tea smallholder was determined by several factors, namely the ability of the people's tea agro-industry actors in: 1) fulfilling the supply of raw materials (tea tops), 2) managing the finances owned, 3) managing the organization, 4) doing product diversification, 5) expanding information networks and connectivity with relevant agencies, 6) continuity in market demand, and 7) continuity in maintaining product quality.